(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
This article analyzes the evolution of the character Giselle’s figure in the film Enchanted (2007), understanding the figure as a narrative element and visual language in the construction of the character. The research investigates how the transformations in clothing accompany the protagonist’s adaptation process, who comes from the world of fairy tales, to the real world, articulating cinema and fashion. As a methodology, an approach is adopted that combines semiotic analysis, film analysis, and fashion image analysis, applied to selected scenes from the film. The analysis identifies references to different periods in fashion history—such as the Victorian Era, the Belle Époque, the fashion of the 1950s and the 2000s—showing that each costume symbolizes stages of the character’s maturation.